Late Quaternary palaeoenvironmental reconstruction of central Tierra del Fuego (Argentina) based on pollen and fungi - Musotto, Lorena Laura (2017)
This paper presents the main palaeoenvironmental results obtained from two sites located in the eastern (La Correntina peat bog) and southern (Terra Australis peat bog) sectors of the Lake Fagnano area, situated at 54° S on the Tierra del Fuego island, at the southernmost extreme of Patagonia. Here, we provide an overview of the postglacial ecosystem and vegetation dynamics on both slopes of the Fuegian Andes by combining palynological records of pollen and fungal remains analyses, supported by radiocarbon datings and multivariate statistics. The pollen data from the two sites indicate initial shrubby and herbaceous vegetation with scattered trees, under drier and colder climate conditions than today. Expansion of Nothofagus forest began about 11,200 cal BP in the Terra Australis area, while an open vegetation of grasslands and shrubs developed around La Correntina site by 11,500 cal BP followed by the establishment of the forest-steppe ecotone after 9400 cal BP. These vegetation changes implied a modification of the climate toward warmer and drier climate conditions than present. At both sites, the predominance of the mycorrhizal Glomus was related to the presence of open ground grassland, indicating relatively dry local conditions. Closed-canopy forests dominated the landscape after 6500 cal BP at Terra Australis, and after 5000 cal BP at La Correntina, suggesting relatively cold and wet environmental conditions. However, the fungal assemblage in Terra Australis shows high abundances of epiphyllous Microthyriaceae, pointing that the Nothofagus trees grew closer than at La Correntina. These findings allow us to conclude that both mires have experienced dissimilar trends in the environmental evolution since Late-glacial times, probably due to their locations in two distinct flanks of the Andean range.